Correlation of Phenolic Content of Multiflora Honey from Malang and Alastuwo to Activity Antioxidant Using DPPH (2.2-Diphenyl-1-Pickrylhydrazyl) - Ahwan Abdul (Journal of Nutraceuticals and Herbal Medicine, 2021)
Honey contains various compounds that function as antioxidants, one of which is phenolic compounds. The purpose of this study was to determine the correlation between the phenolic content of multiflora honey from Malang and Alastuwo on antioxidant activity using the DPPH method (2,2-Diphenyl-1-picrylhydrazyl). Qualitative test of phenolic compounds with FeCl3 color reagent, determination of total phenolic content by UV-Vis spectrophotometry using Folin-Ciocalteu method and antioxidant activity test using DPPH method (2,2-Diphenyl-1-picrylhydrazyl). The results showed that qualitatively Malang and Alastuwo honey contained phenolic compounds. The total phenolic content of Alastuwo honey was 0.0278 ± 0.0010 mg GAE/g and Malang honey was 0.0301 ± 0.0004 mg GAE/g. The results of the antioxidant activity test showed that Alastuwo honey had weak antioxidant activity (IC50 of 393.37 ± 10.28 ppm), Malang honey had moderate antioxidant activity (IC50 of 217.20 ± 6.61 ppm) and vitamin C had strong antioxidant activity. (IC50 is 2.22 ± 0.19 ppm). The total phenolic content of Alastuwo and Malang honey correlates with its antioxidant activity.